Identification and Comprehensive Genome-Wide Analysis of Glutathione S-Transferase Gene Family in Sweet Cherry (Prunus avium) and Their Expression Profiling Reveals a Likely Role in Anthocyanin Accumulation - Sabir, Irfan Ali; Manzoor, Muhammad Aamir; Shah, Iftikhar Hussain; Liu, Xunju; Jiu, Songtao; Wang, Jiyuan; Alam, Pravej; Abdullah, Muhammad; Zhang, Caixi (Frontiers in Plant Science, 2022)
Glutathione S-transferases (GSTs) in plants are multipurpose enzymes that are involved in growth and development and anthocyanins transportation. However, members of the GST gene family were not identified in sweet cherry (Prunus avium). To identify the GST genes in sweet cherry, a genome-wide analysis was conducted. In this study, we identified 67 GST genes in P. avium genome and nomenclature according to chromosomal distribution. Phylogenetic tree analysis revealed that PavGST genes were classified into seven chief subfamily: TCHQD, Theta, Phi, Zeta, Lambda, DHAR, and Tau. The majority of the PavGST genes had a relatively well-maintained exon–intron and motif arrangement within the same group, according to gene structure and motif analyses. Gene structure (introns-exons) and conserved motif analysis revealed that the majority of the PavGST genes showed a relatively well-maintained motif and exons–introns configuration within the same group. The chromosomal localization, GO enrichment annotation, subcellular localization, syntenic relationship, Ka/Ks analysis, and molecular characteristics were accomplished using various bioinformatics tools. Mode of gene duplication showed that dispersed duplication might play a key role in the expansion of PavGST gene family. Promoter regions of PavGST genes contain numerous cis-regulatory components, which are involved in multiple stress responses, such as abiotic stress and phytohormones responsive factors. Furthermore, the expression profile of sweet cherry PavGSTs showed significant results under LED treatment. Our findings provide the groundwork for future research into induced LED anthocyanin and antioxidants deposition in sweet cherries.